1975
DOI: 10.1104/pp.55.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Protein Body Composition in Cuburbita maxima Cotyledons as Determined by Energy Dispersive X-Ray Analysis

Abstract: Energy dispersive x-ray analysis was used to study the composition of certain protein body components in Cucurbita maxima cotyledons. The globoid crystal was rich in phosphorus, potassium, and magnesium. This elemental composition provides further evidence that the globoid crystal in squash cotyledon protein bodies is composed of phytin, a myoinositol hexaphosphoric acid salt of potassium and magnesium. Calcium, a common component of phytin in many species, was absent or present in only trace amounts in the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…With the exception of tiny globoid crystals in very small provascular regions and in epidermal cells, the spot size used was equal to or smaller than the size of the globoid crystal under investigation. Past work with C. maxima (3) showed that some proteinaceous material in the region being analyzed will not contribute greatly, if at all, to the P, K, Ca, and Mg peaks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…With the exception of tiny globoid crystals in very small provascular regions and in epidermal cells, the spot size used was equal to or smaller than the size of the globoid crystal under investigation. Past work with C. maxima (3) showed that some proteinaceous material in the region being analyzed will not contribute greatly, if at all, to the P, K, Ca, and Mg peaks.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues from individual seeds were kept separate so that seed-to-seed variation could be studied. Tissue samples were glutaraldehyde fixed and embedded according to the method of Lott (3). No OS04 was used in these studies since it can bring about extraction of cations and even phosphorus from globoid crystals (6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristically, the EDX spectra of seed globoids show large P and cation (most notably Mg, Ca, K) signals relative to those signals generated from surrounding cytosolic regions (13)(14)(15)(16)(17)(18). The elemental composition of globoids is indicative of the presence of phytin which is composed of salts of myo-inositol hexakisphosphate (14,15).…”
mentioning
confidence: 99%